(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
Safety of an automobile is one of the important areas while designing a vehicle. This paper gives an overall view of the different safety features that are taken care of while designing a vehicle. Available technologies of different active and passive safety features were analyzed. These technical features once incorporated in design not only help in avoiding the accidents but also reduces the fatigue caused to the driver which further mitigates the chances of an accident. Dissipation of the kinetic energy forms the guiding principle while designing all the passive safety features. Crumple zones situated in front and rear absorb this energy upon impact in a predictable way. Safety features such as forward collision warning systems, lane departure warning systems, electronic stability control, anti-lock braking systems, brake assist monitor, brake override, Crumple zones, seatbelts and airbags have been dealt with in detail with an overview of the total vehicle safety.